Desferrioxamine Attenuates Doxorubicin-Induced Acute Cardiotoxicity through TFG-β/Smad p53 Pathway in Rat Model. (30th April 2012) - Al-Shabanah, Othman A.; Aleisa, Abdulaziz M.; Hafez, Mohamed M.; Al-Rejaie, Salim S.; Al-Yahya, Abdulaziz A.; Bakheet, Saleh A.; Al-Harbi, Mohamed M.; Sayed-Ahmed, Mohamed M.
Abstract : Interaction of doxorubicin DOX with iron and the consequent generation of reactive oxygen species (ROS) is a major player in DOX-induced cardiomyopathy. Accordingly, this study has been initiated to investigate the preventive effect of the iron chelator, desferrioxamine (DFX), against DOX-induced acute cardiotoxicity in rats. Male Wistar albino rats were divided into four groups and were injected intraperitoneally (I.P.) with normal saline, a single dose of DOX (15 mg/kg), a single dose of DFX (250 mg/kg) and a combined treatment with DFX (250 mg/kg) 30 min prior to a single dose of DOX, (15 mg/kg). A single dose of DOX significantly increased mRNA expression of TGF- β, Smad2, Smad4, CDKN2A and p53 and significantly decreased Samd7 and Mdm2 mRNA expression levels. Administration of DFX prior to DOX resulted in a complete reversal of DOX-induced alteration in cardiac enzymes and gene expression to normal levels. Data from this study suggest that (1) DOX induces its acute cardiotoxicity secondary to increasing genes expression of TGF- β /Smad pathway. (2) DOX increases apoptosis through upregulation of CDKN2A and p53 and downregulation of Mdm2 gene expression. (3) The preventive effect of DFX against DOX-induced cardiotoxicity is mediated via the TGF- β 1/Smad pathway.